2021
DOI: 10.1002/jor.25022
|View full text |Cite
|
Sign up to set email alerts
|

How much change in pelvic sagittal tilt can result in hip dislocation due to prosthetic impingement? A computer simulation study

Abstract: Developing spinal pathologies and spinal fusion after total hip arthroplasty (THA) can result in increased pelvic retroversion (e.g., flat back deformity) or increased anterior pelvic tilt (caused by spinal stenosis, spinal fusion or other pathologies) while bending forward. This change in sagittal pelvic tilt (SPT) can result in prosthetic impingement and dislocation. Our aim was to determine the magnitude of SPT change that could lead to prosthetic impingement. We hypothesized that the magnitude of SPT chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 31 publications
(91 reference statements)
0
13
0
Order By: Relevance
“…These movements are likely important, as previous computer simulations have shown the effect of these variables on prosthetic impingement. [17][18][19] Lastly, aggregated estimates from published papers were used to simulate the additional positions of daily life. Although these estimates were reported by experienced orthopaedic surgeons and averaged for each position, these numbers do not necessarily represent how a particular patient may move, but still constitute level V evidence.…”
Section: Discussionmentioning
confidence: 99%
“…These movements are likely important, as previous computer simulations have shown the effect of these variables on prosthetic impingement. [17][18][19] Lastly, aggregated estimates from published papers were used to simulate the additional positions of daily life. Although these estimates were reported by experienced orthopaedic surgeons and averaged for each position, these numbers do not necessarily represent how a particular patient may move, but still constitute level V evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Such movement can result in a 10 change in the acetabular anteversion angle, which may place the acetabular prosthesis outside the "safe zone" and cause postoperative dislocation. 21,22 Uemura et al 23 reported that the changes in pelvic sagittal inclination (PSI) from a supine to a standing position would exceed 10 in 8% to 19% of patients with end-stage OA. Abdel et al 24 found that in the majority of cases where dislocation occurred, the cup was positioned in the safety zone, and he suggested that the traditional safety zone may no longer be applicable.…”
Section: Discussionmentioning
confidence: 99%
“…A change in the posterior pelvic tilt of more than 13° from a supine position to standing is defined as adverse pelvic mobility. Such movement can result in a 10° change in the acetabular anteversion angle, which may place the acetabular prosthesis outside the “safe zone” and cause postoperative dislocation 21,22 . Uemura et al 23 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that patients who underwent THA without spine disorder had more changes in acetabular implant orientation due to greater adaptability of the spinopelvic junction than patients who had spine fusion, who might be at risk of posterior dislocation because of less femoral head coverage and less acetabular anteversion. Additionally, the more fused levels, the more acetabular anteversion and inclination decrease (about 1° for each fused group for each value) [ 70 ]. Therefore, it has been proposed by Lazennec et al to evaluate lumbosacral junction using standing and sitting EOS imaging or radiographs in patients with spine fusion in THA planning and follow-up [ 71 , 72 , 73 ], but this attitude is not yet officially recommended.…”
Section: Imaging Follow-up Of Hamentioning
confidence: 99%